Influence of Ru-Ni-Nb combined cathode modification on corrosion behavior and passive film characteristics of Ti-6Al-4V Alloy used for oil country tubular goods. (October 2022) - Liu, Qiang; Zhou, Bo; Zhang, Juantao; Zhang, Weifu; Zhao, Mifeng; Li, Ning; Xiong, Maoxian; Chen, Jialei; Yu, Yang; Song, Sheng-yin
Abstract: A new Ru-Ni-Nb combined cathode modification for Ti-6Al-4V alloy was investigated. There was a multiple blocking mechanism existed in the passivation film of Ru-Ni-Nb modified Ti-6Al-4V alloy, which not only increased the surface potential, but also greatly decreased the number of metastable oxides and point defects in the passive film, and reduced the transport and diffusion process of titanium ions and/or oxygen in the passive film, thus effectively reducing destruction of the passive film and maintaining the stability and integrity of the oxide film, which has excellent corrosion resistance in harsh oil &gas exploration environments. Highlights: A new Ru-Ni-Nb combined cathode modification for Ti-6Al-4V alloy was investigated. This new method not only increases the surface potential, but also forms a multiple blocking mechanism in the passivation film. The content of metastable oxides, point defects and the diffusion process of titanium ions and/or oxygen through the passive film of Ru-Ni-Nb modified Ti-6Al-4V alloy were significantly reduced. Ru-Ni-Nb modified Ti-6Al-4V alloy has better corrosion resistance due to optimized stability, passivation ability and integrity of the passive film.